2016
DOI: 10.1200/jco.2015.64.0862
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy With 4 Gy × 5 Versus 3 Gy × 10 for Metastatic Epidural Spinal Cord Compression: Final Results of the SCORE-2 Trial (ARO 2009/01)

Abstract: Short-course RT with 4 Gy × 5 was not significantly inferior to 3 Gy × 10 in patients with MESCC and poor to intermediate expected survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
88
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 10 publications
3
88
0
3
Order By: Relevance
“…In the present study, improvement of motor deficits by radiation was associated with the dynamic of the development of motor deficits prior to the start of treatment. A slower development was associated with a better functional outcome, which has been described before in other series of patients with MSCC (3,5,25). These results can be explained by the fact that a slower compression of the spinal cord mostly affects the veins and is reversible after radiation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the present study, improvement of motor deficits by radiation was associated with the dynamic of the development of motor deficits prior to the start of treatment. A slower development was associated with a better functional outcome, which has been described before in other series of patients with MSCC (3,5,25). These results can be explained by the fact that a slower compression of the spinal cord mostly affects the veins and is reversible after radiation.…”
Section: Discussionsupporting
confidence: 74%
“…No patient of the 0-1 point group survived 6 months or longer, and the median survival time was only 4 months. Therefore, these patients should receive a short radiation program such as 1×8 Gy or 5×4 Gy in 1 week to avoid spending more of their remaining lifetime receiving treatment than necessary (2)(3)(4)(5)(6)(7)(8). In the group with 2-3 points, all patients lived for 6 months or longer (median survival time >8 months, not yet reached).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of palliative radiotherapy for metastases from solid tumors including bladder cancer have shown that a significant relief of symptoms can be achieved also with short radiotherapy programs that last only one day or one week. This has for example been demonstrated already for irradiation of painful bone metastases, metastatic spinal cord compression and brain metastases (2,3,(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 75%
“…The heterogeneity of treatment regimens used highlights the lack of consensus for optimal palliative management in pediatrics. Whereas the safety and efficacy of a variety of dose and fractionations schedules are reported for palliative RT scenarios in adult patients, including brain metastases, bone metastases, and spinal cord compression, only few retrospective studies exist to describe the clinical experience of palliative RT in the pediatric population. Of these published retrospective studies, each report favorable rates of symptom improvement with palliative RT in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%